The Effect of Using the SQ3R Method Assisted by Digital Story Texts on Improving Critical Thinking Skills in the 'World Window Book' Material for Grade V Students of SD Negeri 104202 Bandar Setia - Nadia Safitri; Rudi Hermansyah Sitorus; Nur Wahyuni; Muhammad Dekar (International Journal of Education and Literature, 2025)
This study aims to examine the effect of using the Survey, Question, Read, Recite, Review (SQ3R) method assisted by digital story texts on students' critical thinking skills in the material "Book of the Window World" of grade V of SD Negeri 104202 Bandar Setia. The background of this study is based on the low critical thinking skills of students due to the dominance of conventional methods that are less varied and minimal use of learning media, especially in Indonesian subjects. This study uses a quantitative approach with a quasi-experimental method and a Nonrandomized Pretest-Posttest Control Group Design. The research subjects consisted of class VA (experimental, n = 22) who received learning with the SQ3R method assisted by digital story texts, and class VB (control, n = 23) who received conventional learning. The pretest results showed that students' initial critical thinking skills were in the moderate category (experimental x ̄ = 67.23; control x ̄ = 51.96). After the treatment, the experimental class' posttest average increased significantly to 82.41, or 15.18 points, while the control class did not experience any significant improvement. A t-test demonstrated a significant difference between the two groups (t count > t table). The study's conclusions indicate that the SQ3R method, aided by digital narrative texts, significantly improved students' critical thinking skills compared to conventional methods.